Aligning clinical research ethics with community-engaged and participatory research in the United States - Eder, Milton (Mickey) (Frontiers in Public Health, 2023)
The professional role in ethical review of research in which boards review proposed research involving human beings continues to evolve. The scholarly literature on institutional review boards in academic centers of the United States, at which a majority of the community engaged and participatory research emanates and is reviewed, suggests the need to implement changes in board education, the infrastructure supporting review, and the accountability of review. The recommendations for change advanced in this perspective involve enhancing reviewer knowledge of local community contexts and developing an infrastructure that supports engagement in and dialogue among individuals involved in community-academic research to inform ethical review and the assessment of review outcomes. Additionally, the recommendation that institutions put an infrastructure in place to sustain community engagement and collaboration can collect and review outcome data related to accountability. The recommendations outlined intend to demonstrate improved alignment between clinical research ethic reviews and community-engaged and participatory research.